Correlations for Heat Transport by Natural Convection of Cylindrical Surfaces Situated One above the Other - Milan Malcho; Jozef Jandacka; Tadeas Ochodek; Jan Kolonicny (Communications, 2015)
The paper presents a new criterion equation for calculating the Nusselt number for heat transport by natural convection from different numbers of cylindrical surfaces of heating sources. Horizontal cylindrical surfaces are situated one above the other and each of them is independently electrically heated by constant power output of Joule heating. Correlation relationships were derived on the basis of tens of measurements of heat outputs of the system of electrically heated horizontal cylindrical surfaces in a thermostatic chamber under defined conditions. The number of cylindrical surfaces, their distance and heat output to the horizontal cylinder varied during measurements. The derived criterion equation is significantly simpler compared to equations corrected by polynomial regression.